Neoliberal technologies of subject formation: a case study of the Duke of Edinburgh's Award scheme - Petersen, Eva Bendix; O'Flynn, Gabrielle (Critical studies in education, 2007)
The hegemony of neoliberalism as an economic and Governmental rationality on a global scale is well documented. How it has come to be that way, and how its relevance is upheld is a complex theoretical and historical-empirical question. This article contributes to the discussion by examining the ways in which neoliberal discourse enters into the production of subjectivity and comes to operate at the level of desire. While subject formation takes place in multiple and contradictory ways, and within and across a multiplicity of social sites, the article focuses on the popular Duke of Edinburgh's Award scheme as a technology of neoliberal subjectification. The article analyses how neoliberal discourse manifests itself in the Award's promotional material and programme and, drawing on qualitative semi-structured interviews, how the Award scheme is taken up by students in a prestigious Australian private girls' school.